Treatment with the Proteasome Inhibitor MG132 during the End of Oocyte Maturation Improves Oocyte Competence for Development after Fertilization in Cattle - You, Jinyoung; Lee, Eunsong; Bonilla, Luciano; Francis, Jasmine; Koh, Jin; Block, Jeremy; Chen, Sixue; Hansen, Peter J. (PLOS ONE, 2012)
Maturation of the oocyte involves nuclear and cytoplasmic changes that include post-translational processing of proteins. The objective was to investigate whether inhibition of proteasomes during maturation would alter competence of the bovine oocyte for fertilization and subsequent development. Cumulus-oocyte complexes were cultured in the presence or absence of the proteasomal inhibitor MG132 from either 0–6 h or 16–22 h after initiation of maturation. Treatment with MG132 early in maturation prevented progression to meiosis II and reduced fertilization rate and the proportion of oocytes and cleaved embryos that became blastocysts. Conversely, treatment with MG132 late in maturation improved the percentage of oocytes and cleaved embryos that became blastocysts without affecting nuclear maturation or fertilization rate. Optimal results with MG132 were achieved at a concentration of 10 µM – effects were generally not observed at lower or higher concentrations. Using proteomic analysis, it was found that MG132 at the end of maturation increased relative expression of 6 proteins and decreased relative expression of 23. Among those increased by MG132 that are potentially important for oocyte competence are GAPDH, involved in glycolysis, TUBA1C, needed for organellar movement, and two proteins involved in protein folding (P4HB and HYOU1). MG132 decreased amounts of several proteins that exert anti-apoptotic actions including ASNS, HSP90B1, PDIA3 and VCP. Another protein decreased by MG132, CDK5, can lead to apoptosis if aberrantly activated and one protein increased by MG132, P4HB, is anti-apoptotic. Finally, the pregnancy rate of cows receiving embryos produced from oocytes treated with MG132 from 16–22 h of maturation was similar to that for control embryos, suggesting that use of MG132 for production of embryos in vitro does not cause a substantial decrease in embryo quality.